2019
DOI: 10.1186/s41938-019-0130-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of bioassay methods in identifying the most virulent entomopathogenic fungal strains to control Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae)

Abstract: Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) is a serious pest of cotton that inflicts huge economic losses. Excessive use of chemical pesticides for its management causes environmental pollution and pesticide resistance. Six bioassay methods and ten entomopathogenic fungal strains (EPFs) were evaluated to find out the suitable bioassay method and the most virulent strain(s) for management of B. tabaci under laboratory and polyhouse conditions. The highest tenderness and survival period (> 30 days) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
2
8
0
1
Order By: Relevance
“…Fungal isolates are effective biological tools against many target pests of controlled and semi-controlled glass-houses without causing remarkable loss to other biocontrol agents and pollinators. Various studies have found entomopathogens as a strong tool of biological control of sucking insect pests (Amnuaykanjanasin et al 2013;Yun et al 2017;El Husseini 2019c;Mohamed 2019;Sain et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Fungal isolates are effective biological tools against many target pests of controlled and semi-controlled glass-houses without causing remarkable loss to other biocontrol agents and pollinators. Various studies have found entomopathogens as a strong tool of biological control of sucking insect pests (Amnuaykanjanasin et al 2013;Yun et al 2017;El Husseini 2019c;Mohamed 2019;Sain et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…There are relatively few whitefly toxicological bioassay studies where multiple methods were compared in the same project, mainly to assess either adult or immature whitefly response [ 14 , 33 ]. Sain et al [ 34 ] found that there was an advantage of using an intact leaf compared to multiple methods using leaf disk or detached leaf bioassays. Our results were similar in that the one detached leaf bioassay used, the dish method, provided the poorest dose response data for whiteflies.…”
Section: Discussionmentioning
confidence: 99%
“…The highest corrected mortality, after 4 days, with the highest concentration was 22.5%. Sain et al (2019) reported that the conidial concentration of C. javanica strains at 10 7 ml −1 caused 77.6-81.1% mortality in second to third instars of B. tabaci nymphs. An LC 50 value of 10 7 spores ml −1 after 4 days of inoculation has been reported against nymphs of the green peach aphid (Myzus persicae) (Kang et al 2018).…”
Section: Resultsmentioning
confidence: 99%